Incorporating an activity schedule during schedule thinning in treatment of problem behavior. (1st July 2021) - Boyle, Megan A.; Bacon, McKenzie T.; Sharp, Danielle S.; Mills, Nathan D.; Janota, Taylor A.
Abstract: We incorporated an activity schedule (MacDuff et al., 1993) into schedule thinning (Hanley et al., 2014) following functional communication training in the treatment of problem behavior of a child with autism, systematically replicating and extending research on activity schedules and schedule thinning. When the activity schedule was introduced, independent engagement increased, rates of communication responses decreased, and problem behavior remained low. Results are discussed in terms of advantages of activity schedules during schedule thinning, conceptual implications for including activity schedules, and directions for future research.